Patterns of Parliamentary Opposition: Empirical Evidence from the Deliberations in the German Bundestag's Committee on European Union Affairs. Issue 1 (19th December 2019) - Albrecht, Frederike; Karlsson, Christer; Persson, Thomas
Abstract: This article examines patterns of oppositional behaviour in the German Bundestag's Committee on European Union Affairs (EAC) for two separate legislative periods (2005–2009 and 2009–2013). The study makes two contributions to previous research. It, first, shed some much-needed empirical light on political opposition in the Bundestag by examining how much and what kind of opposition exists in the German EAC. Secondly, the article examines the differences in oppositional behaviour of the Members of Parliament between the two legislative periods following an institutional reform in 2009 that afforded the Bundestag with increased opportunity structures in Europen Union affairs.